Electrochemical Formation of Germanene: pH 4.5. Issue 7 (1st January 2017) - Ledina, M. A.; Bui, N.; Liang, X.; Kim, Y. -G.; Jung, J.; Perdue, B.; Tsang, C.; Drnec, J.; Carlà, F.; Soriaga, M. P.; Reber, T. J.; Stickney, J. L.
Abstract : Germanene is a single layer allotrope of Ge, with a honeycomb structure similar to graphene. This report concerns the electrochemical formation of germanene in a pH 4.5 solution. The studies were performed using in situ Electrochemical Scanning Tunneling Microscopy (EC-STM), voltammetry, coulometry, surface X-ray diffraction (SXRD) and Raman spectroscopy to study germanene electrodeposition on Au(111) terraces. The deposition of Ge is kinetically slow and stops after 2–3 monolayers. EC-STM revealed a honeycomb (HC) structure with a rhombic unit cell, 0.44 ± 0.02 nm on a side, very close to that predicted for germanene in the literature. Ideally the HC structure is a continuous sheet, with six Ge atoms around each hole. However, only small domains, surrounded by defects, of this structure were observed in this study. The small coherence length and multiple rotations domains made direct observation with surface X-ray diffraction difficult. Raman spectroscopy was used to investigate the multi-layer Ge deposits. A peak near 290 cm −1, predicted to correspond to germanene, was observed on one particular area of the sample, while the rest resembled amorphous germanium. Electrochemical studies of germanene showed limited stability when exposed to oxygen.